Generation of Highly Selective MMP Antibody Inhibitors - Nam, Dong Hyun (Methods Mol Biol, 2018)
Inhibiting individual MMPs of biomedical importance with high selectivity is critical for both fundamental research and therapeutic development. Here we describe the methods for discovery of inhibitory monoclonal antibodies from synthetic human antibody phage display libraries carrying convex paratopes encoded by long complementarity-determining region (CDR)-H3 segments. We demonstrate the application of this technique for isolation of highly specific and potent antibody inhibitors of human MMP-14.